Peran Pemuka Adat sebagai Mediator terhadap Penyelesaian Konflik dalam Proses Perkawinan pada Masyarakat Muna di Sulawesi Tenggara - Intan, Nur (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2018)
The system of social stratification in marriage customs provisions in latently Muna society can generate conflicts between social layers that require completion. This study aims at how the role of traditional leaders as mediators to resolve conflicts in the process of marriage in Muna society in Sulawesi southeast. This research was conducted in Muna Regency, which is in Lawa and Wadaga sub-districts. This type of research, namely the juridical sociological research. Sampling was done by purposive sampling. Data were obtained through interviews and documentation study. The data were analyzed ie qualitatively and presented descriptively. The results showed that the Indigenous Leaders to function as a mediator, facilitator, negotiator, and arbitrator. Practice Indigenous Leaders generally use this together approach, especially in the private and public conflict resolution. Settlement reached by the parties in conflict is the settlement amicably by mediation in order to seek the best solution, it is necessary for the role of Indigenous Leaders acting as mediators with the consideration that they are people who know in depth about the philosophy of Muna customary law, has the authority, charisma, honored, respected, and obeyed his words.